Experiences of Aboriginal Nursing Faculty in Canadian University Schools of Nursing: A Multiple Case Study - Miles, Lynn (My University, 2016)
Aboriginal nursing faculty have a positive impact in the recruitment and retention of Aboriginal nursing students, informing and implementing culturally responsive curricula, and engaging in research that is responsive to the needs of Aboriginal communities. Given the continued health disparities experienced by Aboriginal peoples, there is a need to recruit and retain increased numbers of Aboriginal nursing faculty. However, Aboriginal faculty have experienced racism in academia for decades. A focus on individual factors as opposed to institutional causes has resulted in little effectiveness in resolving experiences of racism. The purpose of this study was to explore the experiences of Aboriginal nursing faculty to determine if and how they experienced institutional racism. A multiple case study approach utilizing an Institutional Racism Framework (Chesler, Lewis & Crowfoot, 2005) was undertaken. Institutional racism was identified in each of the eight cases explored. Two major findings arose from this study. First, although Aboriginal nursing faculty were expected to be the keeper of all Aboriginal knowledge, Aboriginal participants were often not viewed as ‘authentic’ Aboriginal persons at the university. The perception was that by having attained the credentials to be university faculty, the Aboriginal nursing faculty were no longer considered Aboriginal enough to have an authentic voice. Second, Aboriginal nursing faculty experience ‘walking between two worlds’. They felt that they did not fully belong in their home communities. They also identified that they did not feel that they completely belong, or were supported in the university. Rather than identifying as ‘bicultural’, Aboriginal nursing faculty clearly articulated inhabiting this new space situated between cultures. The identification of institutional elements that address or perpetuate institutional racism allowed for recommendations to be determined. The shift from an individual to an institutional perspective allows for an alternative approach to reducing racism experienced by Aboriginal nursing faculty.
Keywords: Aboriginal Nursing Faculty; Institutional Racism